The Arabidopsis zinc finger proteins SRG2 and SRG3 are positive regulators of plant immunity and are differentially regulated by nitric oxide. Issue 1 (7th November 2020) - Cui, Beimi; Xu, Shiwen; Li, Yuan; Umbreen, Saima; Frederickson, Debra; Yuan, Bo; Jiang, Jihong; Liu, Fengquan; Pan, Qiaona; Loake, Gary J.
Summary: Nitric oxide (NO) regulates the deployment of a phalanx of immune responses, chief among which is the activation of a constellation of defence‐related genes. However, the underlying molecular mechanisms remain largely unknown. The Arabidopsis thaliana zinc finger transcription factor (ZF‐TF), S ‐nitrosothiol (SNO) Regulated 1 (SRG1), is a central target of NO bioactivity during plant immunity. Here we characterize the remaining members of the SRG gene family. Both SRG2 and, especially, SRG3 were positive regulators of salicylic acid‐dependent plant immunity. Analysis of SRG single, double and triple mutants implied that SRG family members have additive functions in plant immunity and, surprisingly, are under reciprocal regulation. SRG2 and SRG3 localized to the nucleus and functioned as ethylene‐responsive element binding factor‐associated amphiphilic repression (EAR) domain‐dependent transcriptional repressors: NO abolished this activity for SRG3 but not for SRG2. Consistently, loss of GSNOR function, resulting in increased (S)NO concentrations, fully suppressed the disease resistance phenotype established from SRG3 but not SRG2 overexpression. Remarkably, SRG3 but not SRG2 was S ‐nitrosylated in vitro and in vivo . Our findings suggest that the SRG family has separable functions in plant immunity, and, surprisingly, these ZF‐TFs exhibit reciprocal regulation. It is remarkable that, through neofunctionalization, the SRG family has evolved to become differentially regulated by the key immune‐related redox cue, NO.